The Ideal Refugee: A Study of the Status of LGBTQ Refugees in Iceland - Alexandra Dögg Steinþórsdóttir 1991- (2019)
This thesis analyses the status of LGBTQ refugees and asylum seekers, both in international context and in Icelandic context, respectively. Secondly it questions whether Iceland has a preferred refugee identity, which it admits more readily than others. To accomplish this, the thesis first discusses LGBTQ rights and experience in the international arena, then the refugee and asylum system and policy in Iceland, and finally presents the findings of a series of interviews with people working with LGBTQ refugees, both for advocacy groups and for the government. A qualitative methodological approach is employed, using phenomenological methods to identify and compare shared experiences of the professionals. Seven interviews serve as the foundation for the analysis and data collection which is compared to the theoretical and relevant legal background. The results show that LGBTQ refugees are more vulnerable to social isolation in all stages of the refugee process, discrepancies in the system such as how family reunification laws inadvertently discriminate against LGBTQ refugees, lack of funds and housing pose a security risk and legislation provides space for favouritism in the refugee system despite all the participants rejecting the practice. Idealisms influence the resettlement system and LGBTQ status can be considered as a deciding factor in refugee applications. Finally, the results are that LGBTQ refugee status in Iceland is relatively strong in an international context despite these issues and even if the existence of favouritism in the refugee system is debatable, LGBTQ refugee identity is a likely reason. Í þessari rannsókn er staða hinsegin flóttafólks skoðuð, bæði í alþjóðlegu og íslensku samhengi. Einnig er kannað hvort íslenska ríkið eigi sér svokallað gullinsnið af flóttamanni sem það er líklegra til að veita vernd heldur en öðrum. Ritgerðin byrjar á að ræða réttindi samkynhneigðra og upplifanir á alþjóðavettvangi, síðan flóttamanna- og hælisleitendakerfin á Íslandi. Að lokum eru kynntar niðurstöður ...